2006
DOI: 10.1007/s10038-006-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel heterozygous mutation in the Indian hedgehog gene (IHH) is associated with brachydactyly type A1 in a Chinese family

Abstract: Brachydactyly type A1 (BDA1) is caused by mutations in the Indian hedgehog gene, IHH, on chromosome 2q35-36. In this study, a large five-generation Chinese family with BDA1 was identified and characterized. All affected family members demonstrated significant homogeneous phenotype and some unique clinical features different from those associated with the reported BDA1 mutations in IHH. Linkage analysis showed that the BDA1 gene in the family was linked to marker D2S126 close to IHH with a LOD score of 4.74 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…The absence of an intact zinc site in dHhN remains curious, but perhaps suggests that it is the large substrate-binding cleft rather than the zinc ion itself that is most essential for mediating HhN-Ptc interactions. Indeed, mutation of Hhip D383 to alanine does not completely abolish binding between Hhip and ShhN (Bishop et al 2009;Bosanac et al 2009), and several mutations in the IhhN zinc cleft have been identified recently in BDA1 patients (Liu et al 2006;Byrnes et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The absence of an intact zinc site in dHhN remains curious, but perhaps suggests that it is the large substrate-binding cleft rather than the zinc ion itself that is most essential for mediating HhN-Ptc interactions. Indeed, mutation of Hhip D383 to alanine does not completely abolish binding between Hhip and ShhN (Bishop et al 2009;Bosanac et al 2009), and several mutations in the IhhN zinc cleft have been identified recently in BDA1 patients (Liu et al 2006;Byrnes et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The first group affects the calcium-binding region of Ihh and include E95K, E95G, D100N, D100E, and E131K (22,33). A second category, R128N, T154I, and T130N, interrupts hydrogen-bonding networks formed between IhhN and Asp 872 of CDO or the equivalent residue, Asp 758 , of BOC (34,35). Superposition of IhhN on DhhN in the DhhN⅐Hip structure suggests that these mutations would also disrupt a similar hydrogen-bonding network involving Glu 380 of Hip (32,36) and thus be likely to disrupt interactions between HhN proteins and multiple binding partners.…”
Section: Resultsmentioning
confidence: 99%
“…In one family, the feet were reported to be normal; however, lower limb X-rays were not provided in the paper. 22 The involvement of the phalanges and metacarpals (metatarsals) is quite variable even within the same family. Shortening of the first metacarpal, which is typically a distinguishing feature of Brachydactyly type C is a rare but reported finding.…”
Section: Mutations In Indian Hedgehog That Causes Brachydactyle A-1mentioning
confidence: 99%
“…20,21 The only reported BDA1-causing mutation that was not restricted to codons 95, 100, and 131 of IHH is p.Thr154Ile. 22 All four of these codons are highly conserved ( Figure 1 suggests that they may reside in a region of IHH that is of particular importance and is responsible for the normal functioning of the growth plate during bone development.…”
Section: Introductionmentioning
confidence: 99%